Economic Policy Perspectives for a New German Federal Government - ZG Überblick (Wirtschaftsdienst)
Abstract The eighth New Paradigm Workshop of the Forum New Economy took place from 25 to 27 May. Under the title “Future of the German model II — Perspectives for the next government”, various challenges that will occupy German politics in the coming legislative period were discussed. As with the first New Paradigm Workshop, selected contributions will be summarised in a Wirtschaftsdienst-Zeitgespräch. The contributions from the previous workshop can be found in the Zeitgespräch issue 100(10). The current issue provides insights into new research in the fields of fiscal policy, populism research, financial market regulation, distribution and climate policy